Physiological and self-report methods to the measurement of emotion in tourism. Issue 4 (2nd October 2019) - Hadinejad, Arghavan; Moyle, Brent D.; Kralj, Anna; Scott, Noel
ABSTRACT: There is strong growth in research on tourist emotion, with a substantial scholarly debate emerging, surrounding approaches to measurement. Recently objective physiological methods for measurement of emotion have been applied in the tourism field. However, there are few studies which explore the benefits and limitations of applying physiological and self-report methods to measure emotions. This research aims to compare and contrast physiological and self-report methods to assess emotional responses to tourism marketing stimuli where music was manipulated. This research assessed emotional responses from 37 participants to three tourism advertisements of Iran using four key methods; specifically, FaceReader™, skin conductance, self-report surveys and post hoc interviews. This research found that the light rhythmic music tends to evoke positive emotions and a higher level of emotional arousal in participants than does the traditional Iranian music or a video without music. Physiological and self-report measures of emotional arousal were inconsistent, but both techniques found similar results for assessing the valence of emotions. Thus, results highlight the importance of applying physiological techniques in combination with self-report surveys and post hoc interviews to provide a better and more accurate understanding of emotional experiences.